Africanidades brasileiras na sala de aula: identidades e (re)conhecimentos - Santos Júnior, José Bartolomeu dos (2019)
Our main objective in this work is to analyze Afro-Brazilian identities in content and experiences of students and teachers belonging to the social movements of the State School Coronel José Pinto de Abreu. We seek support in the history of colonial / imperial society to understand the prejudices built on descendants / practitioners of Afro-indigenous cultural manifestations and their strategies for reorganization. In this process of domination / exploitation, the blacks had inserted in their minds a depreciative educational project, inferiorizing and despising their ways of being in the world. Law 11.645 / 2008 and the Racial Equality Statute are some of the devices that attempt to defuse these prejudices, with an emancipatory education, generating equity among all. The school in cities where slave labor was expressive, as in Goiana, is an important space for an increasingly constructive dialogue about a past of oppression, and the present as a challenge based on the legacy of afro-brasilian identities and struggles.